Electromagnetic and acoustic wave tomography direct and inverse problems in practical applications - Blaunstein, Nathan; Yakubov, Vladimir P. 1948-2021; Klokov, Andrey V.; Shipilov, Sergey E.; Sukhanov, Dmitry Ya (Taylor & Francis Group, CRC Press, 2019)
This book discusses the development of radio-wave tomography methods as a means of remote non-destructive testing, diagnostics of the internal structure of semi-transparent media, and reconstruction of the shapes of opaque objects based on multi-angle sounding. It describes physical-mathematical models of systems designed to reconstruct images of hidden objects, based on tomographic processing of multi-angle remote measurements of scattered radio and acoustic (ultrasonic) wave radiation--